Deficient cyclic adenosine 3',5'-monophosphate control in mutants of two genes of Neurospora crassa. - Pall, M L (1981)
Strains of Neurospora crassa mutant in either of two genes, Crisp-1 (cr1) and Frost (fr), showed no increase of cyclic adenosine 3',5'-monophosphate (cyclic AMP) levels when subjected to several treatments which produce large increases of cyclic AMP in wild-type Neurospora. Evidently, the previously reported deficiencies of adenylate cyclase in these mutants were sufficient to block the normal increases. This fact suggests that both mutants could be used to help determine which control phenomena involve cyclic AMP and to interrupt the control of established cyclic AMP-regulated functions. Earlier studies had suggested an interdependence of the cyclic AMP level and the electric potential difference across the plasma membrane of Neurospora. Present experiments, therefore, employed several strains with the cr1 mutation to test for possible roles of cyclic AMP in recovery and oscillatory behavior of the Neurospora membrane potential. The results showed all such phenomena to be normal in the adenylate cyclase-defective strains, which demonstrates that variations of cyclic AMP are not obligatorily involved in the apparent control processes. Evidence is also presented that the induction of both glucose transport system II and the alternative oxidase do not require elevated cyclic AMP levels.